Evaluating the Diagnostic Role of ACR-TIRADS and Bethesda Classifications in Thyroid Nodules Highlighted by Cyto-Histopathological Studies - Eissa, Marwa S.; Sabry, Rania M.; Abdellateif, Mona S. (Experimental and Clinical Endocrinology & Diabetes, 2024)
Objective To evaluate the accuracy of thyroid imaging reporting and data system (ACR-TIRADS) and the Bethesda system for reporting cytopathology (TBSRCP) classifications for identifying or ruling out thyroid malignancy in relation to the gold standard (post-surgical pathology).Methods This cross-sectional study included 573 patients with single or multiple thyroid nodules. Patients were evaluated using the TIRADS and the TBSRCP classification. The data from a cohort of patients who underwent surgery (77/573, 13.4%) were correlated with post-operative pathology and the relevant clinical features of the patients.Results Of 573 patients, 545 (95.1%) were euthyroid, 24 (4.1%) were hypothyroid, and 4 (0.8%) were hyperthyroid; 419 (73.1%) had benign nodules (Bethesda II), 115 (20.1%) had intermediate (Bethesda III, IV), and 39 (6.8%) had Bethesda V and VI nodules. Four-hundred twenty (73.3%) patients were categorized as TIRADS 2,3, and 153 (26.7%) were categorized as TIRADS 4,5. The Bethesda and TIRADS classifications concorded significantly in thyroid nodule diagnosis (K=14.9%, P<0.001).Thyroid malignancy was significantly associated with microcalcification and interrupted halo, while benign nodules were significantly associated with macrocalcification and complete halo type (P=0.041, P=0.005, respectively). The TBSRCP could significantly detect malignant thyroid nodules with a sensitivity, specificity, PPV, and NPV of 64.1%, 98.1%, 85.0%, and 94.1%, respectively (K=88.2%, P<0.001), while the respective values for the TIRADS classification were 63.5%, 76.0%, 84.6%, and 50.0% (K=34.8%, P=0.001).Conclusion The TIRADS and TBSRCP are essential primary steps for evaluating thyroid nodules and both are complimentary. Hence, each patient with thyroid nodules should be evaluated by both approaches before opting for surgery. Highly suspicious TIRADS categories TR4 and TR5 need further evaluation by fine needle aspiration cytology.
Keywords: thyroid; TIRADS; FNAC; TBSRCP; diagnosis; ultrasonography